UJI BEDA KINERJA DAN KOMPETENSI ANTARA GURU BERSERTIFIKASI DAN GURU BELUM BERSERTIFIKASI DI SMPN 02 PECANGAAN JEPARA - Linda Ayu Fitriani; Titik Djumiarti; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2014)
This research aims to analyze the difference in performance and competence among certified teachers and uncertified teachers in SMPN 02 Pecangaan Jepara to see the certification of teachers effectiveness in improved performance and competence of the teacher in the teaching and learning activities in the classroom based on assessment of students as a direct party to obtain services of teachers.This research using a quantitative method that has sort of comparative involving 67 students as respondents taken from the number of students in SMPN 02 pecangaan jeparaBased on the result showed that performance and competence between certified teachers and uncertified teacher are not different.Where the result of independent variable ttest sample of the performance show that, sig (0,184)> α(0,05) and for variables competence sig (0,983)> α(0,05). It is indicated that certification the teacher didn't have significant impact to improve performance and competence of teachers